Constructing a Mainland State in Literature: Perceptions of Venice and Its Terraferma in Marin Sanudo’s Geographical Descriptions - Toffolo, Sandra (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2014)
This article focuses on how, in a time of important political changes, narratives concerning Venice and its mainland state could be constructed and transformed. As case study, three geographical descriptions by the Venetian patrician Marin Sanudo (1466–1536) are analyzed: Itinerarium Marini Sanuti Leonardi filij patricij Veneti cum syndicis Terre Firme, De origine, situ et magistratibus urbis Venetae, and Descriptione de la patria de Friul. Several interwoven themes are treated: the ways Sanudo justified Venice’s rule over a large territory on the Italian mainland, his perception of the links between capital and mainland territory, and his view on the strength of these links. I show that the way Sanudo constructed an image of the Venetian state had its own internal dynamics. As shown in the chronological development present in Sanudo’s works, his representation of the Venetian state is partly a reaction to the political circumstances, but not a direct reflection of them.